Abdominal imaging - Aasen, S. (Reference, 2013)
In this book a team of leading experts come together to provide a comprehensive overview of modern imaging of the abdomen and pelvis, with detailed sections on both gastrointestinal and genitourinary imaging. Each chapter has an identical structure and focuses on a particular organ or organ system, allowing the reader to approach the field one topic at a time. Indications for a variety of imaging techniques and examination protocols are clearly described, and the imaging features of normal anatomy and pathologic entities are depicted in an abundance of high-quality images. Care is taken to consider all recent technical developments and new indications, and the diagnostic performance of different imaging modalities is carefully compared. It is anticipated that this book will come to be regarded as the standard work of reference on abdominal and pelvic radiology.